2017
DOI: 10.1080/21678707.2017.1366310
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials of exon skipping in Duchenne muscular dystrophy

Abstract: Introduction: DMD is most common form of severe childhood muscular dystrophy. The large size of the DMD gene challenges DNA repair or replacement. However, experimental in vitro and in vivo studies using antisense oligonucleotides (AONs) showed that exon skipping could result in production of a truncated dystrophin protein with potential to modify the dystrophic phenotype. This provided the impetus for clinical testing as discussed in this review. Area covered: Clinical trials were begun using alternative stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In view of frequently encountered mutation of exon 49 and 50, Exon 51 skipping approach might benefit a large proportion [45/80 (56.25%)] of our study group. Before exon-skipping therapeutics took shape, Wilton in 1999 showed using mdx mouse model, that AONs can remove the mutation in the exon resulting in increased dystrophin production by its repetitive administration [35].…”
Section: Discussionmentioning
confidence: 99%
“…In view of frequently encountered mutation of exon 49 and 50, Exon 51 skipping approach might benefit a large proportion [45/80 (56.25%)] of our study group. Before exon-skipping therapeutics took shape, Wilton in 1999 showed using mdx mouse model, that AONs can remove the mutation in the exon resulting in increased dystrophin production by its repetitive administration [35].…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized placebo-controlled phase 2 clinical trials demonstrated improvement of the 6-minute walk test (6MWT) in children treated with 6 mg/kg/week drisapersen administered subcutaneously for a period of 24 weeks the effect which was maintained, albeit with reduced significance, 48 weeks after treatment [87]. However results were not reproducible in the phase III placebo-controlled trial that followed and no dystrophin production was detectable by western blotting in treated patient's muscle obtained through biopsy [88,89] although an increase in sarcolemmal dystrophin myofiber was observed by immunohistochemistry [[90], [91], [92]]. Adverse effects such as skin fragility at the site of injection, proteinuria and presence of alpha microalbumin in the urine occurred and became more prominent when dose was scaled up to 9 mg/kg/week, therefore, the US Food and Drug Administration (FDA) declined approval on the basis that ‘the standards of effectiveness have not been met’ [90].…”
Section: Asos In Exon Skipping Clinical Trials Targeting Dmdmentioning
confidence: 99%
“…However results were not reproducible in the phase III placebo-controlled trial that followed and no dystrophin production was detectable by western blotting in treated patient's muscle obtained through biopsy [88,89] although an increase in sarcolemmal dystrophin myofiber was observed by immunohistochemistry [[90], [91], [92]]. Adverse effects such as skin fragility at the site of injection, proteinuria and presence of alpha microalbumin in the urine occurred and became more prominent when dose was scaled up to 9 mg/kg/week, therefore, the US Food and Drug Administration (FDA) declined approval on the basis that ‘the standards of effectiveness have not been met’ [90]. However, intensified efforts to overcome such toxicity problems have led to the development of optimized stereopure ASOs.…”
Section: Asos In Exon Skipping Clinical Trials Targeting Dmdmentioning
confidence: 99%
See 1 more Smart Citation
“…ASO-based therapeutic approaches to promote targeted exon skipping and restore transcript reading frame have been successfully tested in other genetic conditions. Eteplirsen, an ASO with a morpholino backbone, has recently received accelerated approval from the FDA for the treatment of Duchenne muscular dystrophy 38 .…”
Section: Discussionmentioning
confidence: 99%